2016
DOI: 10.7150/jca.15200
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Malignant Processes are Regulated by Pax-5 Through the Disruption of FAK Signaling Pathways

Abstract: The study of genetic factors regulating breast cancer malignancy is a top priority to mitigate the morbidity and mortality associated with this disease. One of these factors, Pax-5, modulates cancer aggressiveness through the regulation of various components of the epithelial to mesenchymal transitioning (EMT) process. We have previously reported that Pax-5 expression profiles in cancer tissues inversely correlate with those of the Focal Adhesion Kinase (FAK), a potent activator of breast cancer malignancy. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Previously, miR-135b-5p has been well documented as a tumor suppressor [33][34][35] or oncogene [36][37][38] in breast cancer, but less is known about the expression and function of miR-135b-3p. In case that both 5p and 3p strands are functional and not degraded, despite targeting different mRNAs, they might cooperate temporally and result in a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, miR-135b-5p has been well documented as a tumor suppressor [33][34][35] or oncogene [36][37][38] in breast cancer, but less is known about the expression and function of miR-135b-3p. In case that both 5p and 3p strands are functional and not degraded, despite targeting different mRNAs, they might cooperate temporally and result in a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the function of PLK4 in NB tumorigenesis and metastasis remains to be elucidated. The transformation of a cell with epithelial characteristics into one with mesenchymal traits occurs during the epithelial–mesenchymal transition (EMT) process, which has been uncovered to play a significant role in tumor development 25 , and the activation of EMT is commonly reflected a vested feature of malignancy 26 , 27 . EMT was also reported to be associated with the migratory and invasive properties of human NB cells 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 9 downregulated and 2 upregulated genes were selected for validation using qRT-PCR, and they were all consistent with the findings of RNA-seq. Interestingly, we found that COMP, ITGA11, COL4A6, RAC2, and CCND2 were associated with the FAK signaling pathway 18 - 20 , which plays a fundamental role in cancer progression and metastasis 21 , 22 . The focal adhesion proteins such as FAK, regulate cell spreading, adhesion, migration, proliferation and angiogenesis, and FAK expression correlates with tumor invasion, metastatic potential and poor disease outcome 23 .…”
Section: Discussionmentioning
confidence: 92%